Natureza e naturalização da tecnologia : panorama informacional na sociedade pós-medial - Crippa, Giulia (Palabra Clave.)
After almost thirty years of capillary use of information and communication technologies (ICTs), society has naturalized its presence. However, living with ICTs does not mean understanding the scale of the paradigmatic changes they have made globally. The purpose of this article is to discuss the premises and the implications of the socio-cultural transformations imposed by the new media, observing some of their effects in the social, economic and political spheres. The methodology used is of a qualitative and bibliographic nature, with a discussion elaborated through the tools of Cultural Studies and Sociology of the Imaginary of Durandian matrix. Our results, from the movie Avatar, consider the phenomena of changes and transformations provided in all social spheres by the naturalization of technology in contemporary discourses. In the discussion, a historical path is offered on the evolution of the media until the definition of a post-medial paradigm; the effects of the naturalization of ICTs at the social, economic and political levels are observed; the effects on the imaginary caused by the use of improper terminologies in the ideology and rhetoric of innovation are analyzed; some responses offered by society and politics to the problems raised by ICTs are outlined. We conclude that there is a need for critical appropriation of ICTs, which must necessarily be denatured again to be the object of study with a broader focus and not just application.